1988
DOI: 10.1111/j.1469-7610.1988.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Dentine Lead Levels, Intelligence, School Performance and Behaviour

Abstract: The relationship between dentine lead levels and measures of cognitive ability was examined for a birth cohort of New Zealand children studied until the age of 9. There were small, consistent and stable correlations between dentine lead measures and all measures of cognitive ability including intelligence, word recognition and teacher ratings of school performance. After adjustment for the effects of confounding covariates, sample selection factors and possible reverse causal effects, the correlations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…There is some support for this proposal, with evidence that verbal IQ is particularly susceptible to a number of changes in the prenatal environment, such as maternal cigarette use 17 and exposure to polychlorinated biphenyl 18 and lead. 19 Future studies that examine the association between maternal hypertensive diseases of pregnancy and the full cognitive profile of offspring will build on the findings presented here.…”
Section: Discussionmentioning
confidence: 79%
“…There is some support for this proposal, with evidence that verbal IQ is particularly susceptible to a number of changes in the prenatal environment, such as maternal cigarette use 17 and exposure to polychlorinated biphenyl 18 and lead. 19 Future studies that examine the association between maternal hypertensive diseases of pregnancy and the full cognitive profile of offspring will build on the findings presented here.…”
Section: Discussionmentioning
confidence: 79%
“…One of the more rigorous and well-designed studies in Pocock's review was that by Fergusson et al [77]. Using a longitudinal design, the authors found no change in IQ following adjustment for covariates including gender.…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
“…All the studies to be cited find that the IQof the high-lead group is lower than that of the low-lead group by 2-11 points. Some find that the difference between groups is still significant when confounders are allowed for (Fergusson, Fergusson, Horwood & Kinzett, 1988;Hansen, Trillingsgaard, Beese, Lyngbye & Grandjean, 1988;Hatzakis ^/«/., 1988;Needleman ^/a/., 1979;Yule, Urbanowicz, Lansdown & Millar, 1984); others find that statistical significance disappears (Lansdown, Yule, Urbanowicz & Hunter, 1986;Smith, Delves, Lansdown, Clayton & Graham, 1983;Landrigan ^^ «/., 1975;McNeil & Ptasnik, 1975;Ratcliffe, 1977;Winneke, Hrdina & Brockhaus, 1982). I have reviewed these studies in more detail elsewhere, and could not account for the disparities on the basis of details of methodology (Taylor, in press).…”
Section: Developmental Neuropsychiatrymentioning
confidence: 99%
“…Some analyses have tried to allow for this statistically. For example, Fergusson et al (1988) used the symptom of pica as an index of self-exposure, and concluded that this pathway could not account for the whole of the lead-behaviour association. The argument, however, is not sufficient.…”
Section: Developmental Neuropsychiatrymentioning
confidence: 99%
See 1 more Smart Citation